(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The article argues that, given the complex and abstract nature of physics, providing students with opportunities for practical experience and collaborative problem-solving is crucial for improving the effectiveness of physics education. Furthermore, the authors provide recommendations for integrating project-based learning within modern educational methodologies to increase the engagement and success of students in the study of physics.